2011
DOI: 10.1007/s12098-011-0532-8
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of HIV Exposed Infants: Experience of a Regional Pediatric Center for HIV in North India

Abstract: HIV infection is being under-diagnosed during pregnancy. Exposed infants have a high mortality and high prevalence of malnutrition. There is an urgent need for standardizing care of exposed infants to promote follow-up and prevent mortality by offering feeding counseling and ensuring early infection detection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
3

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 20 publications
0
5
3
Order By: Relevance
“…With onset of HIV infection, the divergence in growth profile in our infants occurred within 4–6 weeks of life and persisted through one year of life. Other studies have noted differences occurring around 3 months of age [13,16,17], but most have noted the difference in growth between HIV-infected and uninfected occurring by one year of life [8,9,27]. LAZ score among infected infants in our study was lower by 0.35 at 6 months and 0.81 at 12 months.…”
Section: Discussioncontrasting
confidence: 65%
See 1 more Smart Citation
“…With onset of HIV infection, the divergence in growth profile in our infants occurred within 4–6 weeks of life and persisted through one year of life. Other studies have noted differences occurring around 3 months of age [13,16,17], but most have noted the difference in growth between HIV-infected and uninfected occurring by one year of life [8,9,27]. LAZ score among infected infants in our study was lower by 0.35 at 6 months and 0.81 at 12 months.…”
Section: Discussioncontrasting
confidence: 65%
“…In a retrospective study of 162 HIV-exposed infants at a Regional Pediatric Center for HIV in Delhi, prevalence of wasting and stunting was 50.5% and 48.8%, respectively [27]. While our prevalence of stunting was comparable to that in this study, the wasting was lower in our study.…”
Section: Discussioncontrasting
confidence: 46%
“…Four studies reported on percentages of children who died, were lost to follow-up/defaulted or transferred out before starting ART [13][16], and one study reported the proportion of patients lost to follow-up [17]. A small study of 24 children reported on the proportion of children who died, with no children lost to follow-up [18]. The estimates ranged between 3.2% and 45.8% for mortality, 0.0% and 37% for loss to follow-up and 3.4% and 4.6% for transfer out ( Table S1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Different eligibility criteria will influence the number of people deemed eligible for ART initiation while for children in advanced clinical stage it was not necessary to measure CD4 cells. Apart from two studies [12], [18] the follow-up ended before the new guidelines were published. Our study could thus not determine the impact of the change in guidelines on retention in care.…”
Section: Discussionmentioning
confidence: 99%
“…The risk of transmission increases with the duration of breast feeding, although in a nonlinear fashion. [5] Antiretroviral prophylaxis given soon after birth to all HIV exposed infants is effective in reducing MTCT which forms the basis of post exposure prophylaxis strategy. Infant ARV prophylaxis is also highly effective in reducing transmission through breast milk.…”
Section: Introductionmentioning
confidence: 99%